STRUKTUR FRASA NOMINAL ATRIBUTIF DALAM BAHASA SASAK - Mahendra, Dian; Winarti, Daru (Universitas Hamzanwadi, 2022)
This research aims to identify the structure of attributive nominal phrases in Sasak. The data was obtained by observing method and analyzed by direct constituent method. The results of data analysis show that the structure of attributive nominal phrases in Sasak is divided into six types. The results of the study show that the structure of attributive nominal phrases in Sasak is divided into six types. These types are attributive nominal phrases with attributes in the form of 1) nouns, 2) numerals, 3) verbs, 4) adjectives, 5) demonstratives, and 6) prepositional phrases.Keywords: Sasak language, attributive nominal phrases, functional structures of phrases, attributive structures of phrases